2008
DOI: 10.1016/j.devcel.2007.11.014
|View full text |Cite
|
Sign up to set email alerts
|

The Kinesin-8 Motor Kif18A Suppresses Kinetochore Movements to Control Mitotic Chromosome Alignment

Abstract: During vertebrate cell division, chromosomes oscillate with periods of smooth motion interrupted by abrupt reversals in direction. These oscillations must be spatially constrained in order to align and segregate chromosomes with high fidelity, but the molecular mechanism for this activity is uncertain. We report here that the human kinesin-8 Kif18A has a primary role in the control of chromosome oscillations. Kif18A accumulates as a gradient on kinetochore microtubules in a manner dependent on its motor activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

56
477
5
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 299 publications
(563 citation statements)
references
References 36 publications
56
477
5
3
Order By: Relevance
“…It revealed that metaphase sister-kinetochore pairs undergo semiregular oscillations along the spindle axis, a phenomenon that had been previously described in a qualitative manner (Skibbens et al, 1993). Our automated assay further showed that the speed of kinetochore movements is controlled antagonistically by two microtubule-depolymerases located at kinetochores, the kinesins MCAK and Kif18a, consistent with previous studies on Kif18a (Jaqaman et al, 2010;Stumpff et al, 2008). However, the depletion of either depolymerase did not affect the semi-regularity of sister-kinetochore oscillations, indicating that other components must be controlling the regularity of chromosome movements.…”
Section: Kinetochores Key Drivers Of Chromosome Movementssupporting
confidence: 90%
“…It revealed that metaphase sister-kinetochore pairs undergo semiregular oscillations along the spindle axis, a phenomenon that had been previously described in a qualitative manner (Skibbens et al, 1993). Our automated assay further showed that the speed of kinetochore movements is controlled antagonistically by two microtubule-depolymerases located at kinetochores, the kinesins MCAK and Kif18a, consistent with previous studies on Kif18a (Jaqaman et al, 2010;Stumpff et al, 2008). However, the depletion of either depolymerase did not affect the semi-regularity of sister-kinetochore oscillations, indicating that other components must be controlling the regularity of chromosome movements.…”
Section: Kinetochores Key Drivers Of Chromosome Movementssupporting
confidence: 90%
“…KIF18A can also make tubulin rings 113 and has an extended loop-2 reminiscent of the kinesin-13 family (BOX 2), which supports the idea that it can bend tubulin to drive depolymerization. These effects on microtubule dynamics likely cause the reported changes in the speed and amplitude of kinetochore oscillations following depletion of KIF18A, and the resulting severe chromosome congression defect 106,114,115 . The first single molecule mechanics data for KIF18A were recently reported,…”
Section: Kinetochore-mediated Pushing and Pullingmentioning
confidence: 99%
“…79 The use of RNAi to knockdown KIF18A expression resulted in aberrantly elongated spindle microtubules, loss of tension across sister kinetochores, activation of the spindle checkpoint, and mitotic arrest. 4 T lymphocytes that has high homology with KIF18A.…”
Section: Kinesin-8 Familymentioning
confidence: 99%